Interlacing of the poetic texts in the Dada’iyah; intertextual reading (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research deals with a clear phenomenon in a poetic text, overflowing with woven expressive contexts, and loaded with broad imaginary cards, which was called by many names, including: (Al-Dada’iyah) by the Abbasid poet Abu Al-Shis Al-Khuza’i, which is the phenomenon of interlacing and overlapping texts in the research. These relations are under the concept of intertextuality and traditional intertextuality, which gave the literary discourse artistic characteristics and a creative interaction in which different intertextualities fused into a single strand, towards: stylistic manifestations, intellectual amalgamations, literary proverbs and artistic contents.In order for the study to reach a state of systematic integration, the researcher set out to divide his research into a preface and two main topics, namely:1-The problem of space proportions of the poem.2- Verbal and syntactic overlapping.3 -Semantic and moral entanglement.